2010
DOI: 10.1128/jvi.01598-10
|View full text |Cite
|
Sign up to set email alerts
|

Autographa californica Multiple Nucleopolyhedrovirus Ac92 (ORF92, P33) Is Required for Budded Virus Production and Multiply Enveloped Occlusion-Derived Virus Formation

Abstract: The Autographa californica multiple nucleopolyhedrovirus orf92 (p33), ac92, is one of 31 genes carried in all sequenced baculovirus genomes, thus suggesting an essential function. Ac92 has homology to the family of flavin adenine dinucleotide-linked sulfhydryl oxidases and is related to the ERV/ALR family of sulfhydryl oxidases. The role of ac92 during virus replication is unknown. Ac92 was associated with the envelope of both budded and occlusion-derived virus (ODV). To investigate the role of Ac92 during vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 36 publications
3
81
0
2
Order By: Relevance
“…However, to our surprise, and in contrast to WT ODVs, containing mostly multiple nucleocapsids with only a few single nucleocapsids, very few or no multiple-nucleocapsid ODVs were observed in occlusion bodies from the two dnapol mutants. Although the mechanisms of nucleocapsid envelopment in ODVs probably differ, the lack of multiple-nucleocapsid ODVs in the ABC rep double point mutant was similar to that of the nonviable Ac92 and viable Ac23 knockout viruses (53,54). Moreover, the drug-resistant viruses generated polyhedra which were larger than those generated by the WT rep virus.…”
mentioning
confidence: 82%
“…However, to our surprise, and in contrast to WT ODVs, containing mostly multiple nucleocapsids with only a few single nucleocapsids, very few or no multiple-nucleocapsid ODVs were observed in occlusion bodies from the two dnapol mutants. Although the mechanisms of nucleocapsid envelopment in ODVs probably differ, the lack of multiple-nucleocapsid ODVs in the ABC rep double point mutant was similar to that of the nonviable Ac92 and viable Ac23 knockout viruses (53,54). Moreover, the drug-resistant viruses generated polyhedra which were larger than those generated by the WT rep virus.…”
mentioning
confidence: 82%
“…Therefore, it is difficult to propose putative sulfhydryl oxidase substrates in baculoviruses on the basis of information derived from NCLDVs. However, despite their distant relationship, common to both baculoviruses and NCLDVs is a severe drop in infectious virion production upon the elimination of sulfhydryl oxidase activity (25,31,39,48), suggesting a fundamental role for disulfide formation in both cases. The molecular defects that lead to a dramatic drop in the number of infectious baculovirus particles produced in the absence of Ac92 have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an enzyme capable of catalyzing disulfide formation was identified in baculoviruses (28), a group of large double-stranded DNA viruses not classified as NCLDVs (21). The baculovirus sulfhydryl oxidase enzyme, one of a core group of conserved baculovirus gene products, is essential for virion assembly and thus for virus propagation (31,48), similarly to its counterparts in NCLDVs (25,39).…”
mentioning
confidence: 99%
“…Also a knockout (KO) of ac43 appeared to increase the number of SNPVs in occlusion bodies, and co-infection of the ac43 KO virus with a virus encoding ac43 restored the predominance of the MNPV morphotype [24]. It has also been shown that deletion of ac92, a core gene encoding a sulfhydryl oxidase, results in virions that resemble the SNPV morphotype [25]. However, they are not infectious, indicating that they have a structural defect in one or more viral or possibly cellular proteins required for the production of viable virions.…”
Section: Nucleocapsid Aggregation: Multiple Versus Single Nucleocapsimentioning
confidence: 99%